The interface between arts practice and research: Attitudes and perceptions of Australian artist-academics - Wright, D.; Bennett, Dawn; Blom, D. (Routledge, 2010)
Whilst an academic working in the arts may have been appointed as a consequence of artistic accomplishment and a capacity to teach, the research that underpins such work is an intrinsic part of its production and also needs to be recognised. In Australia, the ability of the artist-academic to translate research into a form that is respected and rewarded is an issue of contention. This paper gathers responses to this issue. Perceptions of and attitudes to creative work as research are canvassed alongside life decisions arising from those perceptions and attitudes. This research occurs in the context of a new Australian framework for the evaluation of research. This framework offers some recognition of the research that supports creative practice. Thus, the long-standing experience of compromise reported by the Australian artist-academics interviewed for this study are discussed alongside new policies that seek to construct methodologies for its amelioration.